Género, poder y literatura en la España contemporánea - Alonso Valero, Encarna (Acta Hispanica, 2010)
This paper analyzes the images of power and the consecration mechanisms that can befound in the pathways of several political women in the first third of the 20th century in Spain.To that end, this work considers concepts like the idea of merit and the idea of exceptionscreation, among others.The construction of national feminine myths is also analyzed, giving a detailed overviewabout the utilization of music and literature as effective resources to conform those miths.